Enhancing Students’ Reading Comprehension through the Implementation of TAR (Text Around The Room) Technique - Kasmiri, Utin Ainun; Riyanti, Dwi; Fitriarti, Urai Mimmi Variami Nurul (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
This classroom action research aimed to investigate the implementation of the "text around the room" technique in enhancing students' reading comprehension skills, as well as identify the factors that influence the improvement of their reading comprehension abilities. The study was conducted over two cycles, with each cycle consisting of two sessions following the plan, action, observation, and reflection framework. The participants in this research were 34 eleventh-grade students in one of the schools in Pontianak. Data were collected through various means, including observation sheets, field notes, questionnaire, multiple-choice reading tests, and achievement scores. The findings of this study indicate that the implementation of the "text around the room" technique resulted in significant improvements in students' reading comprehension. Additionally, the study identified three key factors that influenced students' comprehension in reading: (a) the selection of appropriate reading materials, (b) student motivation, and (c) the teacher's approach to engaging with the students.